(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the meaning and importance of the concept of perception, which is one of the main categories of epistemology, and its role in understanding the characteristics of space and time. In addition, today the level of perception and the factors affecting it are analytically described. The need for the mechanism of interpersonal perception in achieving sustainable development is revealed.